2010
DOI: 10.2118/126072-pa
|View full text |Cite
|
Sign up to set email alerts
|

Smart-Well Production Optimization Using an Ensemble-Based Method

Abstract: Summary Ensemble methods have been applied successfully in assisted history matching and in production optimization. In history matching, the ensemble Kalman filter (EnKF) has been used to estimate the values of hundreds of thousands of variables from various types of data. In production optimization, an ensemble-based method has been used to estimate optimal control settings for problems with thousands of control variables. In both cases, relatively small numbers of random realizations are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Previously these types of model-based optimization strategies (proactive strategies) were presented in several publications (refer, for instance, (Yeten et al, 2004;Obendrauf et al, 2006;Emerick and Portella, 2007;Chen et al, 2009;van Essen et al, 2010;Su and Oliver, 2010) and showed good results. We do believe that it is difficult and inefficient to implement the aforementioned approaches in full field reservoir models directly, because they would result in large, multidimensional and timeconsuming optimization problems.…”
Section: Framework For Modeling and Optimizationmentioning
confidence: 99%
“…Previously these types of model-based optimization strategies (proactive strategies) were presented in several publications (refer, for instance, (Yeten et al, 2004;Obendrauf et al, 2006;Emerick and Portella, 2007;Chen et al, 2009;van Essen et al, 2010;Su and Oliver, 2010) and showed good results. We do believe that it is difficult and inefficient to implement the aforementioned approaches in full field reservoir models directly, because they would result in large, multidimensional and timeconsuming optimization problems.…”
Section: Framework For Modeling and Optimizationmentioning
confidence: 99%
“…Therefore, it is urgent to establish a practical methodology for inter-well connectivity estimation while coupling A viable alternative is approximation of the gradient by an ensemble optimization technique known as EnOpt, which has received appealing attention over the past years by reservoir engineers after the pioneering work of Chen et al [24,25]. Using the deterministic or standard EnOpt, hybrid constrained optimization problems were resolved by generalized non-linear programming algorithms [7,[26][27][28]. Do and Reynolds [29] analyzed the deterministic EnOpt and demonstrated its close connection with other stochastic gradient algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Predecessors to the EnOpt method were proposed by Lorentzen et al (2006) and Nwaozo (2006), whereafter Chen (2008) and Chen et al (2009) gave systematic descriptions of the method, as mostly used today. Thereafter, several publications addressed applications and computational aspects of the method; see, for example, Chaudhri et al (2009), Chen and Oliver (2010), Su and Oliver (2010), Leeuwenburgh et al (2010), and Chen and Oliver (2012). In a recent paper, Do and Reynolds (2013) demonstrate that EnOpt can be interpreted as a member of a broader class of approximate-gradient methods that also includes the simultaneous-perturbation stochastic approximation method.…”
Section: Introductionmentioning
confidence: 99%